2019
DOI: 10.3390/ijerph16203846
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sociodemographic and Psychological Variables Involved in Sleep Quality in Nurses

Abstract: Background: Sleep quality is related to health and quality of life and can lead to the development of related disorders. This study analyzed the sociodemographic and psychological factors related to sleep quality in nurses. Methods: The sample comprised 1094 nurses who were assessed according to the Pittsburgh Sleep Quality Index, the Rosenberg Self-esteem Questionnaire, the Goal Content for Exercise Questionnaire, the Brief Emotional Intelligence Inventory, and the Three-Factor Eating Questionnaire-R18. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
16
0
3
Order By: Relevance
“…Our study showed that a low level of self-care self-regulation was a significant predictor of poor global sleep quality, as well as the subcomponents of subjective sleep quality and daytime dysfunction. These findings were similar to the previous report that motivation for physical exercise and eating behaviors (such as uncontrolled eating and emotional eating) were linked to poor sleep quality in nurses [ 2 ]. Self-care can be conceptualized as a self-regulation process that activates health promotion behaviors and inhibits health risk behaviors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that a low level of self-care self-regulation was a significant predictor of poor global sleep quality, as well as the subcomponents of subjective sleep quality and daytime dysfunction. These findings were similar to the previous report that motivation for physical exercise and eating behaviors (such as uncontrolled eating and emotional eating) were linked to poor sleep quality in nurses [ 2 ]. Self-care can be conceptualized as a self-regulation process that activates health promotion behaviors and inhibits health risk behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…However, due to the nature of the work, nurses are at a higher risk for decreased sleep quantity and quality, as well as continuous sleep deprivation [ 1 ]. Fatigue resulting from poor sleep tends to reduce nurses’ ability to concentrate and make correct decisions, leading to the possibility of errors and injuries [ 2 , 3 ]. For example, risk of medication errors was associated with poor quality of sleep among nurses [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…When reviewing the results obtained by other researchers, it can be observed that they indicate different levels of global self-esteem and life satisfaction among the groups of respondents, sometimes being quite diverse [ 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Velmurugan et al proved that 65.3% of the surveyed nursing students revealed moderate self-esteem, while 22.9% had low and only 11.9% had high levels of self-esteem [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear whether sleep, as an important recovery factor, is related to nurse resilience. Sleep quality, as an essential health indicator, has a significant impact on nurses' work performance and personal life (Pérez-Fuentes, Molero Jurado, Simón Márquez, & Gázquez Linares, 2019). Sleep disturbance is related to increased age, family dependents, unhealthy eating, lack of physical activity and low emotional intelligence (Pérez-Fuentes et al, 2019).…”
Section: What Does This Paper Contribute To the Wider Global Clinicalmentioning
confidence: 99%